1994
DOI: 10.1073/pnas.91.15.6795
|View full text |Cite
|
Sign up to set email alerts
|

Rates and patterns of chloroplast DNA evolution.

Abstract: The chloroplast genome (cpDNA) of plants has been a focus of research In plant molecular evolution and systematics. Several features of this genome have facilitated molecular evolutionary analyses. First

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
262
1
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 392 publications
(303 citation statements)
references
References 44 publications
(43 reference statements)
31
262
1
2
Order By: Relevance
“…Furthermore, the only significant recent migration detected is from southwestern Europe into Central Europe, and not the other way around. Unless we posit that the Iberia-specific genetic variation evolved rapidly since an introduction (and this is unlikely due to the low mutation rate of cpDNA (Clegg et al, 1994)), the genetic diversity observed in Iberian populations is not compatible with introduction from Central Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the only significant recent migration detected is from southwestern Europe into Central Europe, and not the other way around. Unless we posit that the Iberia-specific genetic variation evolved rapidly since an introduction (and this is unlikely due to the low mutation rate of cpDNA (Clegg et al, 1994)), the genetic diversity observed in Iberian populations is not compatible with introduction from Central Europe.…”
Section: Discussionmentioning
confidence: 99%
“…We included all insertion or deletion events (indels) in our data set and coded them as either present or absent. We are aware that non-coding regions of the cpDNA are prone to repeated independent evolution of the same indels (Clegg et al 1994). Independently derived indels probably had little e¡ect on our topology because ¢ve out of the seven indels were autapomorphic and the topology of the cpDNA phylogeny when all indels were deleted was almost identical to the topology when all indels were included but it was less well resolved.…”
Section: Methodsmentioning
confidence: 99%
“…Exclusion of these characters did not change the general topological structure of the trees. The nature of the evolution of chloroplast sequences in non-coding regions is complex (Clegg et al 1994), and we sometimes found two to four adjacent bases that appeared to have mutated in tandem. Therefore, we limited the e¡ect of these regions on our phylogenetic estimation by coding them as single changes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, inaccurate calibration will bias the resulting estimates for other divergences. Equally seriously, however, heterogeneous rates of evolution among lineages are well known (3)(4)(5)(6)(7), and a failure to recognize such heterogeneity can compromise resulting estimates of divergence times. Inadequate sampling of taxa, coupled with rate heterogeneity, can compound the problem.…”
mentioning
confidence: 99%